Pay to play: what does PISA participation cost in the US?. Issue 3 (3rd May 2020) - Engel, Laura C.; Rutkowski, David
ABSTRACT: Much attention has been given to the Organization for Economic Co-operation and Development's (OECD) Program for International Student Assessment (PISA) and its effects in different education systems, including the United States. This paper begins to address a major gap in this literature by focusing on the costs of participation in PISA. The paper draws on content analysis of official documents and budgets, as well as qualitative interviews with select government officials at federal and state levels. It details costs in three categories: direct overhead to the OECD, national implementation, and in-kind or human burden. As such, the paper details information on costs of PISA, important for eventual cost–benefit frameworks that may be useful for continued policy deliberations over US participation in PISA and other international large-scale assessments.